Measuring CP-violating observables in rare top decays at the LHC - Saha, Pratishruti (2016)
In this paper we consider CP-violating new-physics contributions to the decay t→bb¯c. We examine the prospects for detecting such new physics at the LHC, which requires studying the process gg→t(→bb¯c)t¯(→b¯ℓν¯). We find two observables that can be used to reveal the presence of CP-violating new physics in t→bb¯c. They are (i) the partial-rate asymmetry and (ii) the triple-product correlations involving the momenta of various particles associated with the interaction. A Monte Carlo analysis is performed to determine how well these observables can be used to detect the presence of new physics, and to measure its parameters. We find that there is little difficulty in extracting the value of the relevant new-physics parameter from the partial-rate asymmetry. For the triple-product correlations, we test multiple strategies that can be used for the extraction of the corresponding combination of new-physics parameters.